Does your lab use social media?: Sharing three years of experience in science communication - Pavlov, AK; Amelie Meyer; Rosel, A; Cohen, L; King, J; Itkin, P; Negrel, J; Gerland, S; Hudson, SR; Dodd, PA; de Steur, L; Mathisen, S; et al. (2018)
Effective science communication is essential to share knowledge and recruit the next generation of researchers. Science communication to the general public can, however, be hampered by limited resources and a lack of incentives in the academic environment. Various social media platforms have recently emerged, providing free and simple science communication tools to reach the public and young people especially, an audience often missed by more conventional outreach initiatives. While individual researchers and large institutions are present on social media, smaller research groups are underrepresented. As a small group of oceanographers, sea ice scientists, and atmospheric scientists at the Norwegian Polar Institute, we share our experience establishing, developing, and maintaining a successful Arctic science communication initiative (@oceanseaicenpi) on Instagram, Twitter, and Facebook. The initiative is run entirely by a team of researchers with limited time and financial resources. It has built a broad audience of more than 7,000 followers, half of which is associated with the team’s Instagram account. To our knowledge, @oceanseaicenpi is one of the most successful Earth sciences Instagram accounts managed by researchers. The initiative has boosted the alternative metric scores of our publications and helped participating researchers become better writers and communicators. We hope to inspire and help other research groups by providing some guidelines on how to develop and conduct effective science communication via social media.